Ethnic variation in the correlation between waist to height ratio and total daily insulin requirement in children with type 1 diabetes: a cross‐sectional study. Issue 2 (4th February 2016) - Uday, Suma; Gorman, Shaun; Feltbower, Richard G; Mathai, Mathew
Abstract : Introduction: Total daily insulin required to achieve glycaemic control in type 1 diabetes (T1D) depends on numerous factors. Correlation of insulin requirement to body mass index and waist circumference has been variably reported in the literature and that of waist‐to‐height ratio has not been studied. Aims: To study the correlation between daily insulin requirement [total daily dose (TDD)] and waist‐to‐height ratio (WHtR) in a multiethnic population. Methods: A cross‐sectional study of children (5–18 years) with T1D attending a diabetes clinic in a multiethnic population in Bradford, UK was conducted. Physical measurements were undertaken in the clinic setting and data collected from case notes and patients/carers. Results: Sixty nine patients with mean age 12.7(±3.1) yr, duration of diabetes 5.4(±3.5) yr and hemoglobin A1c (HbA1c) 80(±18)mmol/mol(9.5 ± 1.6%) were recruited. Nearly 54% (n = 37) were white and 46% were non‐white (29 Asian Pakistani; 1 Indian; 2 mixed White Afro‐Caribbean). The two groups had similar demographics and disease profiles. Non‐whites compared with whites had a higher prevalence of obesity (15 vs 5%, p < 0.01), family history of type 2 diabetes (T2D) (49% vs. 33%), microalbuminuria (22% vs. 11%, p < 0.05) and deprivation (mean index of multiple deprivation score 42 vs. 30, p < 0.001). WHtR and TDD were poorly correlated in the whole group. There was however a significant positive correlation in Caucasians (r = 0.583, N = 37, p < 0.01) and a negative correlation in Asian Pakistanis (r = −0.472, N = 32, p < 0.01); with a significant negative correlation seen in subjects with relatives with T2D (r = −0.86, N = 6, p = 0.02). Conclusions: The variation in correlations highlights that the two ethnic groups behave differently and should therefore be studied separately with regards to factors influencing insulin requirements with careful consideration to the presence of parental IR. Further prospective studies are required to explore the reasons for these differences.